Translation Procedures of Cultural Words in One of the Best Movies of All Times - Rahmawati, Maya (Universitas Islam Negeri Raden Intan Lampung, 2018)
This paper aims to describe the translation strategies used in translating cultural words found in the subtitle of Godfather Movies (I and II). Godfather is one of best of all time movies America has ever had. It contains a lot of cultural words worth to notice. Since subtitle is limited both in term of duration and space, it is interesting to find out how the cultural words are translated to be displayed in the subtitle. The researcher gathered the data by watching the movie, spotting the cultural words, and then writing the translation displayed in the subtitle. Using qualitative approach and through comparative method the researcher analyzed the data. The result of this study shows that the subtitler used five procedures in translating cultural words: naturalization, transference, functional equivalence, cultural equivalence, and modulation. The frequently used procedure among them is transference. This research also investigates the parameters influencing the subtitler’s decision in choosing the translation strategies to tranlate cultural words. It was found that there were six influencing parameters: monocultural, transcultural, specific media constraint, centrality of reference, co-text, intersemiotic redundancy. Considering the influencing factors as well as choosing proper translation procedures could minimize the translation problems arised in subtitling.